EGFR-T790M mutation associated with acquired resistance to first-generation EGFR tyrosine kinase inhibitors in Vietnamese Non-Small-Cell Lung Cancer patients: EGFR-T790M mutation with acquired resistance to first-generation EGFR tyrosine kinase inhibitors in non-small cell lung cancer - Hoan, Le; Nguyen, Ngoc Cuong; Khanh Chi, Tran; Tran Huy Thinh,; Van Khanh, Tran; Thi Tra My, Thieu (Vietnam Journal of Science and Technology, 2024)
Background: non-small cell lung cancer (NSCLC) patients who had epidermal growth factor receptor (EGFR) mutations sensitive to EGFR tyrosine kinase inhibitors (TKIs) had a high response rate to target therapies. Epidermal growth factor receptor (EGFR) T790M mutation is the most common mechanism of acquired resistance to first-generation EGFR TKIs. Objective: The aim of this study was to analyze the incidence of EGFR T790 mutation, the progression-free survival (PFS) in the patients who progress on the first‑ generation EGFR‑TKIs. This study also investigates the correlation between T790M mutation and clinical, subclinical features, progression-free survival of NSCLC Vietnamese patients.Patients and methods: We analyzed 66 NSCLC patients who had acquired resistance to first-generation EGFR-TKIs. The clinical data, PFS and the mechanism of acquired resistance were obtained. The Kaplan-Meier method and the log-rank test were used to analyze the PFS and compare between subgroups of patient characteristics. The correlations between the patient’s characteristics and EGFR-T790M mutation status were analyzed by Chi-square and Fisher’s exact tests.Results: At the progressive period, EGFR T790M mutation was detected in 54.5% of patients. The median PFS were 14.48 ± 3.9 months (range: 8- 26 months). Patients who were older than 60 years old or had comorbidities had significantly shorter PFS than the subgroups without (P≤0.05). The age, gender, smoking status, comorbidities, pathological features were not significantly correlated with the development of EGFR-T790M (P > 0.05). The average PFS was not significantly different between the EGFR-T790M group and the non-EGFR-T790M group (P=0.642).Conclusion: In our cohort study, more than half of all patients had T790M mutation after being treated with first-generation EGFR TKIs. Age and comorbidities were associated with PFS but the EGFR-T790M mutation was not correlated with PFS.